ANALISIS PENGARUH ROA DAN CR TERHADAP PBV DENGAN DPR SEBAGAI VAIABEL INTERVENING - Ningfira Gitaningtyas; Umrotul Khasanah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Company value is a form of company achievement seen from the point of view of several parties such as investors who attribute the value of a company to its share price. There are several factors that can influence the firm value, including profitability, liquidity and dividend policy. In this study using a quantitative approach. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020 by using "purposive sampling" a sample of 51 companies was obtained. The analysis technique used is multiple linear regression and path analysis with the help of SPSS 16.0 . software. The results showed that (1) profitability had no significant effect on dividend policy, (2) liquidity had no significant effect on dividend policy, (3) profitability had no significant effect on firm value, (4) liquidity had no significant effect on firm value, (5 ) dividend policy has no significant effect on firm value (6) profitability through firm value has a significant effect on dividend policy, (7) liquidity through firm value has a significant effect on dividend policy.